THEORETICAL AND PRACTICAL ASPECTS OF EXCLUSIVE RIGHTS TO A WORK MADE FOR WORK IN THE EDUCATIONAL SPHERE - Valeria B. Zolotova (Russian Studies in Law and Politics)
Purpose. The purpose of the article is to study the establishment of fundamental facts that determine the possibility of creating an official work in the educational field, as well as to identify the main mechanisms for protecting the rights of subjects of emerging legal relations, which is due to a number of prerequisites characterizing the relevance of the stated topic. Among them, the gradual commercialization of education and the growing need to protect the results of intellectual work of authors are noted. The subject of the study is regulatory legal acts that establish and disclose the specifics of the grounds for the emergence of an employer’s exclusive rights to an official work, as well as practice-oriented materials in the context of the field under consideration.